2013
DOI: 10.4161/gmcr.26408
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-derived field resistance to Cassava brown streak disease persists across the vegetative cropping cycle

Abstract: Cassava brown streak disease (CBSD) is currently considered the most important disease of cassava in East Africa and a significant threat to food security in the region. 1 CBSD is caused by two distinct virus species: Cassava brown streak virus (CBSV) and Ugandan Cassava brown streak virus (UCBSV), both of which belong to the genus Ipomovirus, family Potyviridae, and possess a ssRNA genome of messenger sense.2,3 Both viruses are transmitted by whiteflies (Bemisia tabaci), resulting in CBSDsymptomatic plants ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 10 publications
0
22
0
1
Order By: Relevance
“…These qualities make TME 204 an ideal target for improvement within the VIRCA project, which aims to bring CMD- and CBSD-resistant planting material to smallholder farmers in East Africa (Taylor et al, 2012). We previously reported field resistance to CBSD generated from an inverted repeat construct carrying the CP of UCBSV (p718) (Ogwok et al, 2012; Odipio et al, 2014). While high levels of resistance to the homologous virus species was achieved in p718 transgenic plants, resistance to CBSV was restricted to two lines that accumulated CP-derived siRNAs at very high levels (Ogwok et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These qualities make TME 204 an ideal target for improvement within the VIRCA project, which aims to bring CMD- and CBSD-resistant planting material to smallholder farmers in East Africa (Taylor et al, 2012). We previously reported field resistance to CBSD generated from an inverted repeat construct carrying the CP of UCBSV (p718) (Ogwok et al, 2012; Odipio et al, 2014). While high levels of resistance to the homologous virus species was achieved in p718 transgenic plants, resistance to CBSV was restricted to two lines that accumulated CP-derived siRNAs at very high levels (Ogwok et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Storage roots were weighed on a digital scale and each root was sliced transversely along their length into five pieces. Each slice was visually assessed for presence and severity of CBSD necrosis on a 1–5 scale (Ogwok et al, 2012; Odipio et al, 2014), adapted from that reported by Hillocks et al (1996). Storage root CBSD incidence was expressed as (a) percentage of plants per line that showed CBSD symptoms in their storage roots and (b) number of roots per line showing CBSD symptoms expressed as a percentage of total number of roots harvested.…”
Section: Methodsmentioning
confidence: 99%
“…In cassava improvement, hpRNA and antisense silencing procedures have been employed mostly in virus control [52][53][54][55][56]. An indirect approach where the hpRNA is used to knockdown the expression of V-ATPase A, an enzyme that provides force for many transport processes, has been used to control whitefly vectors of CMGs and CBSVs [57,58].…”
Section: Hairpin Dsrna Co-suppression and Antisense Rna Silencingmentioning
confidence: 99%
“…While consumers may be hesitant to eat transgenic papaya containing a viral coat-protein gene, they may be surprised to know that they are eating complete virus particles in fruit harvested from non-transgenic, infected trees, including fruit from cross-protected trees. RNAi provides control of other destructive viruses of crops, including the viral complexes that attack cassava in East Africa [22,82], soybean [83], and summer squash [84], and others [47,85].…”
Section: Silencing Essential Pathogen Genesmentioning
confidence: 99%